(untitled) (Journal of Engineering, 2003)
the concept of limit equilibrium and enab e only the calculation of the critical height or the minimum factor of safety of a slope. These methods are not usually concerned with the stress distribution within a slope either above or below assumed surfaces of failure. This task can be done through the finite element method. In this paper, this method is used for the analysis of embankments. It was found that a good agreement could be obtained between the simple non-linear elastic-plastic finite element analysis, adopted in this paper, and sophisticated analyses which deal with plastic behavior of soils. This can be done when choosing the appropriate material parameters.